2009
DOI: 10.1152/ajpcell.00345.2008
|View full text |Cite
|
Sign up to set email alerts
|

Propofol inhibits pressure-stimulated macrophage phagocytosis via the GABAA receptor and dysregulation of p130cas phosphorylation

Abstract: Surgical stress and anesthesia result in systemic immunosuppression. Propofol, a commonly used anesthetic agent, alters immune cell functions. Previously, we demonstrated that extracellular pressure increases macrophage phagocytosis. We hypothesized that propofol might influence pressure-induced macrophage phagocytosis in monocytes from patients undergoing surgery. Pressure (20 mmHg above ambient pressure) augmented phagocytosis in monocytes from non-propofol-anesthetized patients but reduced phagocytosis in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Through the activation of the GABA receptors, propofol exerts various pharmacological effects, including the inhibition of chemotaxis, phagocytosis, ROS generation, and/or cytokine synthesis in monocytes and macrophages (8,9). Another research has demonstrated that human neutrophils express GABA B , but few GABA A receptors (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the activation of the GABA receptors, propofol exerts various pharmacological effects, including the inhibition of chemotaxis, phagocytosis, ROS generation, and/or cytokine synthesis in monocytes and macrophages (8,9). Another research has demonstrated that human neutrophils express GABA B , but few GABA A receptors (41).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that propofol suppresses chemotaxis, phagocytosis, the generation of reactive oxygen species (ROS), and/or the synthesis of cytokines by monocytes and macrophages, which are mediated by activation of the g-aminobutyric acid (GABA) A receptor (8,9); reduces the mitochondria potential (10); and inhibits the AKT/IKKb/NF-kB pathways (11). Propofol impairs the chemotaxis and respiratory burst of neutrophils in response to fMLF (12,13).…”
mentioning
confidence: 99%
“…2729 We previously also reported that propofol (2,6-diisopropylphenol) stimulates macrophage phagocytosis but reverses pressure-stimulated macrophage phagocytosis. 30 Propofol is known to alter the functions of immunocompetent cells as well as to decrease pro-inflammatory cytokine production and iNOS expression in LPS-stimulated mouse macrophages. 3133 .…”
Section: Introductionmentioning
confidence: 99%
“…As monocytes are not as efficient in performing the effector functions of macrophages, including phagocytosis of dead cells (62,63), it is possible that propofol exposure resulted in the uncontrolled expansion of neutrophilic abscesses as a result of reduced macrophage populations and the associated reduction in the phagocytosis of neutrophil corpses. In addition to the drug's potential effects on monocyte differentiation, in vitro studies have shown that exposure to propofol decreases phagocytosis of latex beads in human microglial cell culture (64) and in human THP-1 macrophage cell lines (26). We speculate that the combined effects of propofol on inhibition of monocyte differentiation and impaired phagocytosis contribute to the diffuse and extensive abscess formation observed in the kidneys of drug-treated animals.…”
Section: Discussionmentioning
confidence: 82%